Innate lymphoid cells type 3 in cancer - Castillo-González, Raquel; Valle-Noguera, Ana; Gomez-Sánchez, Maria José; Xia, Pu; Cruz-Adalia, Aranzazu (Frontiers in Immunology, 2022)
Cancer is a multifactorial chronic illness caused by a combination of genetic and environmental factors. A tumor is more than just a collection of cancer cells, it also contains infiltrating and resident host cells that are constantly interacting with it. Innate lymphoid cells (ILCs) have been recently found to be within the tumor and its microenvironment in close relationship with cancer cells. Although ILCs lack an antigen-specific receptor, they can respond to environmental stress signals, aiding in the fast orchestration of an early immune response. They are tissue resident cells mostly located in mucosa and first barrier organs that have been mainly studied in the defense against pathogens, lymphoid development, and tissue repair, however, current research has begun to elucidate their involvement in carcinogenesis. Nevertheless, among all ILCs, ILC3s have been found to be the most controversial in terms of tumor immunity. It has been found that they enhance anti-tumor immunity by detecting cancerous cells and helping lymphocytes infiltrate tumors. However, some recent studies have revealed that IL-23 stimulating ILC3s may promote tumor growth. In this review, we have incorporated the most recent studies on the involvement of ILC3s in cancer development to offer an overview of the role of ILC3s in cancer emphasis on their particular activity in several organs primarily in the mucosa, but also in breast, pancreas, liver, and skin, realizing that their role likely depends on the tissue microenvironment and the subtype of ILC3s.